Systematical approach in evaluation of LC method for determination of raloxifene hydrochloride and its impurities employing experimental design - B. JanÄiÄ StojanoviÄ; T. RakiÄ; B. SlavkoviÄ; N. KostiÄ; A. VemiÄ; A. MalenoviÄ (Elsevier, 2013)
Method validation presents a detailed investigation of analytical method and provision of the evidence that the method, when correctly applied, produces results that fit to the purpose. In order to achieve the method validation scope efficiently, experimental design presents a very useful tool. The greatest benefits of such approach could be seen in robustness testing through the provision of very useful data about the control of the chromatographic system during the routine application. In this paper, robustness testing of the LC method proposed for the determination of raloxifene hydrochloride and its four impurities was done employing PlackettâBurman design. Applying this design, the effect of five real factors (acetonitrile content, sodium dodecyl sulfate content, column temperature, pH of the mobile phase and flow rate) on the corresponding resolution factors was investigated through twelve experiments. Furthermore, the insignificance intervals for significant factors were calculated and the parameters for system suitability tests were defined. Eventually, the other validation parameters were tested and the effectiveness of the proposed analytical method with a high degree of accuracy was confirmed. Keywords: Experimental design, Method validation, Raloxifene hydrochloride, Impurities, Liquid chromatography